Discovery of Novel Task-3 Channel Blockers Using a Pharmacophore-Based Virtual Screening - Reyes-Parada, M (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
TASK-3 is a two-pore domain potassium (K2P) channel highly expressed in the hippocampus, cerebellum, and cortex. TASK-3 has been identified as an oncogenic potassium channel and it is overexpressed in different cancer types. For this reason, the development of new TASK-3 blockers could influence the pharmacological treatment of cancer and several neurological conditions. In the present work, we searched for novel TASK-3 blockers by using a virtual screening protocol that includes pharmacophore modeling, molecular docking, and free energy calculations. With this protocol, 19 potential TASK-3 blockers were identified. These molecules were tested in TASK-3 using patch clamp, and one blocker (DR16) was identified with an IC50 = 56.8 ± 3.9 µM. Using DR16 as a scaffold, we designed DR16.1, a novel TASK-3 inhibitor, with an IC50 = 14.2 ± 3.4 µM. Our finding takes on greater relevance considering that not many inhibitory TASK-3 modulators have been reported in the scientific literature until today. These two novel TASK-3 channel inhibitors (DR16 and DR16.1) are the first compounds found using a pharmacophore-based virtual screening and rational drug design protocol. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.